Massive Transformative Purpose (MTP) as moderator in the relationship between Culture of Experimentation and Autonomy - Vizcaíno, Antonio de Jesús; Aguilar Ruiz, Alfredo (Mercados y Negocios, 2024)
The present research seeks to measure the relationship between the culture of experimentation and autonomy and the relationship between both variables when moderated by the organization’s massive transformative purpose (MTP). This quantitative and exploratory research was conducted through a questionnaire for decision-makers in 43 medium and large IT companies in Jalisco. The results reveal a significant positive relationship between the culture of experimentation and autonomy, corroborating the first hypothesis of this research. However, according to the analyses to calculate the degree of moderation of the massive transformation purpose variable (moderator variable) to adjust the relationship between the culture of experimentation and autonomy, the results showed that there are no significant relationships, which rejects the second hypothesis of this research.